Chromosomal and morphological taxonomy of a new species of black fly in the genus Metacnephia (Diptera: Simuliidae) from Western Anatolia, Turkey - Şirin, Umit D.; Adler, Peter H. (Zootaxa, 2015)
A new species of black fly collected in April from streams 950–1000 m above sea level in Western Anatolia, Turkey, is described on the basis of females, males, pupae, larvae, and polytene chromosomes. Metacnephia phrygiensis new species is structurally and chromosomally distinct from all other known species of the genus, particularly in having unique fixed inversions in chromosomal arms IL and IIIL and a fenestrated cocoon.